High temperature mechanical properties of diffusion welded alloy 800H - Jong-Bae Hwang; Injin Sa; Eung-Seon Kim; Dong-Hyun Lee (Nuclear Engineering and Technology)
High temperature mechanical properties of diffusion welded Alloy 800H was investigated to fabricate a printed circuit heat exchanger (PCHE) for high temperature reactor (HTR) systems. Surface treatment was performed on Alloy 800H to transform the solubility product (Ksp) to exceed the reaction quotient (Q). The surface treatment facilitated the grain boundary migration across the interface. The yield strengths exceeded the values described in ASME Section III Division 5 Table HBB-I-14.5 up to 760 °C, while the tensile strengths were comparable to Table HBB-3225-1 up to 700 °C. At 760 °C, the tensile strength was ∼30 MPa lower than the code. The stress-to-rupture values exceeded the expected minimum stress-to-rupture values of Alloy 800H described in Table HBB-I-14.6C. The ductility of the diffusion weldment acquired from the tensile test was comparable to the as-received Alloy 800H. Meanwhile, the formation of the secondary precipitates on the interface during the stress-to-rupture test deteriorated the ductility of the diffusion weldment, which induced intergranular fracture.